Seroprevalence of SARS‐CoV‐2‐specific antibodies in Sydney after the first epidemic wave of 2020. Issue 4 (3rd February 2021) - Gidding, Heather F; Machalek, Dorothy A; Hendry, Alexandra J; Quinn, Helen E; Vette, Kaitlyn; Beard, Frank H; Shilling, Hannah S; Hirani, Rena; Gosbell, Iain B; Irving, David O; Hueston, Linda; Downes, Marnie; et al.
Abstract: Objectives: To estimate SARS‐CoV‐2‐specific antibody seroprevalence after the first epidemic wave of coronavirus disease 2019 (COVID‐19) in Sydney. Setting, participants: People of any age who had provided blood for testing at selected diagnostic pathology services (general pathology); pregnant women aged 20–39 years who had received routine antenatal screening; and Australian Red Cross Lifeblood plasmapheresis donors aged 20–69 years. Design: Cross‐sectional study; testing of de‐identified residual blood specimens collected during 20 April – 2 June 2020. Main outcome measure: Estimated proportions of people seropositive for anti‐SARS‐CoV‐2‐specific IgG, adjusted for test sensitivity and specificity. Results: Thirty‐eight of 5339 specimens were IgG‐positive (general pathology, 19 of 3231; antenatal screening, 7 of 560; plasmapheresis donors, 12 of 1548); there were no clear patterns by age group, sex, or location of residence. Adjusted estimated seroprevalence among people who had had general pathology blood tests (all ages) was 0.15% (95% credible interval [CrI], 0.04–0.41%), and 0.29% (95% CrI, 0.04–0.75%) for plasmapheresis donors (20–69 years). Among 20–39‐year‐old people, the age group common to all three collection groups, adjusted estimated seroprevalence was 0.24% (95% CrI, 0.04–0.80%) for the general pathology group, 0.79% (95% CrI, 0.04–1.88%) for the antenatal screening group, and 0.69% (95% CrI, 0.04–1.59%) for plasmapheresis donors. Conclusions: Estimated SARS‐CoV‐2 seroprevalence was below 1%, indicating that community transmission was low during the first COVID‐19 epidemic wave in Sydney. These findings suggest that early control of the spread of COVID‐19 was successful, but efforts to reduce further transmission remain important.